Shape Optimizing of a Sleeping Policeman - Pedersen, Niels L. (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
The shape of a sleeping policeman (speed bumps/speed humps) is optimized with respect to the response characteristic of a car going over the bump. The objective is that the ride is as pleasant as possible when the bump is passed below the speed limit, while being unpleasant when the driver is going too fast. The shape of the bump is controlled by a number of amplitudes of some basic functions that are orthogonal in the sense that each contributes something new to the design space. Optimization is performed with numerical sensitivities, from a 2D multibody system simulation, and the results show that it is possible to achieve great improvements in the bump design. The optimization method is not specialized to a specific mechanism and can be used to treat other multibody systems for which a change in response characteristics is required.